Dystocia due to bulldog calf in a cross bred cow - Kumar, Ajeet; HONPARKHE, M; DHALIWAL, G S (The Indian Journal of Animal Reproduction, 2007)
Bulldog calf is a rare condition in bovines and develops due to autosomal recessive genes. The present communication puts on record, a case of dystocia due to bulldog calf in a cross-bred cow.